Resource separation in dynamic logic of propositional assignments - Boudou, Joseph; Herzig, Andreas; Troquard, Nicolas (Journal of logical and algebraic methods in programming, 2021)
We extend dynamic logic of propositional assignments by adding an operator of parallel composition that is inspired by separation logics. We provide an axiomatization via reduction axioms, thereby establishing decidability. We also prove that the complexity of both the model checking and the satisfiability problem stay in PSPACE.